Analisis performa bilah taper dengan airfoil GOE 796 pada turbin angin sumbu horizontal TSD-500 di PT Lentera Bumi Nusantara - Raditya Elfa Pratama; Bobie Suhendra (Jurnal Teknik Mesin Indonesia, 2022)
Indonesia's electricity needs are increasing from year to year, but the availability of fossil fuels such as oil and coal is decreasing, so that new and renewable energy sources are needed as a solution to overcome the problem. One of the renewable energy sources that can be utilized and has great potential is wind energy. The purpose of this study was to determine the optimal taper blade with airfoil for a micro-scale horizontal axis wind turbine. In this study, horizontal axis wind turbine blades with GOE 796 airfoil were tested using a cooging-less PMSG generator in order to achieve high efficiency at minimum wind speeds. The design of the GOE 796 Airfoil Taper blade has a radius of 1 m, a chord width of 34-74 mm, with a twist angle of 5.66-11.66°. The results of the analysis of the performance of the Taper GOE 796 Airfoil blade with a maximum wind speed of 10 m/s has optimal performance at TSR 6.5 with a Coefficient Power (Cp) of 35%, producing a maximum power of 670 W at a rotation speed of 620 rpm and a torque of 10.3 Nm.